1986
DOI: 10.3109/02713688608995174
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ascorbate in the retina, subretinal fluid and pigment epithelium

Abstract: The posterior segment of the eye was divided into four compartments: retinal cytosol (R), subretinal fluid on the retinal surface (S/R), retinal pigment epithelial (RPE) cytosol, and subretinal fluid on the RPE surface (S/RPE). The volume of each compartment was estimated from the dilution of creatinine (in the extraction buffer) by the endogenous tissue fluid. The ascorbate concentrations in R, S/R, S/RPE, and RPE were 20.6, 12.3, 3.7, and 5.8 mg/dl respectively. Dehydroascorbate was observed only in the RPE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…[1][2][3][4] Its concentration in the matrix may be estimated from the amount of IRBP in the eye and volume of the subretinal space to be between 20 and 100 M in mammals. [5][6][7][8] IRBP is thought to play a critical role in mediating the transport of retinoids between the rod photoreceptors and RPE. The role of IRBP in the retinoid visual cycle has been recently reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Its concentration in the matrix may be estimated from the amount of IRBP in the eye and volume of the subretinal space to be between 20 and 100 M in mammals. [5][6][7][8] IRBP is thought to play a critical role in mediating the transport of retinoids between the rod photoreceptors and RPE. The role of IRBP in the retinoid visual cycle has been recently reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…In the vitreous cavity, the collagen and hyaluronic acid that make up the gel phase of the vitreous remain trapped in situ as a result of inherent physical characteristics, whereas the smaller molecular constituents are ultimately drawn through the interstices of the neural retina as part of the The first two authors contributed equally to this work. bulk flow generated by the active clearing of fluid from the subretinal space by the retinal pigment epithelium (RPE; Lai et al, 1986;Marmor, 1990). These smaller molecules therefore contribute to the local microenvironment of not only the vitreous cavity but, to some extent, the retina and subretinal space as well.…”
mentioning
confidence: 99%
“…Despite the potential for overlap in the molecular species present in both the vitreous and subretinal space, these microenvironments generally differ in terms of the relative concentration of small molecules (Lai et al, 1986;Lutty et al, 1996;Saint-Geniez and D'Amore, 2004) as well as a multitude of other considerations, all of which could potentially play a role in determining donor cell engraftment following transplantation. In previous work, we have shown that aqueous humor augments the growth of cultured rat retinal precursor cells when added as a supplement to epidermal growth factor (EGF)-containing proliferation medium (Yang et al, 2006a).…”
mentioning
confidence: 99%
“…Under normal conditions, we found that ascorbic acid exists in the reduced form in the neural retina and aqueous humor, but mostly in the oxidized form (dehydroascorbic acid, or DHA) in the RPE and choroid (19,30). After a period of light stress, the amount of reduced ascorbic acid declined in the retina while DHA in the RPE and choroid increased.…”
Section: Photooxidation Of Ascorbic Acid In the Retinal Pigment Epithmentioning
confidence: 89%